A kinetic comparison of running on treadmill and overground surfaces: an analysis of plantar pressure - Lee, J.; Chung, M.; Mok, K.; Hong, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The purpose of this study was to compare the plantar pressure in treadmill and overground running. It aimed to investigate whether treadmill is a suitable surface to carry out running shoe cushioning test. Fourteen male volunteers were recruited to run on four different running conditions i.e. treadmill, tartan, grass, and concrete with controlled running speed. A mobile plantar pressure measuring system was employed and peak pressure was measured. The results showed that the plantar pressure of treadmill running was different to that of overground running in total foot, medial midfoot, lateral midfoot and lesser toes.